Addressing Potential Conflict among University Students during Collaborative Tasks - Bunmi Isaiah Omodan; Chiggo Skosana (MDPI AG, 2023)
This study addresses potential conflicts during collaborative tasks among university undergraduate students and presents strategies to mitigate such conflicts at a university in South Africa. Drawing on the unique context of South Africa, characterised by its rich cultural diversity and historical challenges, Social Identity Theory (SIT) was used to theorise the study within a transformative paradigm, qualitative approach and participatory research design. Ten undergraduate students were sampled and interviewed. Thematic analysis was employed to make sense of the data. The study found that a lack of a culture of open dialogue and clear guidelines and expectations leads to conflict, and the study also found that promoting a culture of open dialogue and establishing clear guidelines and expectations during collaborative projects can help prevent potential conflicts among university undergraduate students during collaborative engagement. The study concludes that promoting a culture of open dialogue and fostering establishing clear guidelines and expectations provide undergraduate students with the tools to manage group conflicts.